Ultrasound-assisted enzymatic hydrolysis of ham processing by-products for taurine recovery and protein hydrolysate production - Anim Ujong; Ajay Mittal; Nigel Brunton; Carlos Alvarez; Brijesh K. Tiwari; Shay Hannon; Uma Tiwari (Food Chemistry, 2026)

188Re-SIRT Cold Kit: A Promising and Affordable Solution for Hepatocellular Carcinoma - Sejal Chopra; Naveen Kalra; Yamini Mathur; Swathy Krishnan; Komalpreet Kaur; Anupriya Chhabra; Yogesh Rathore; Harish Bhujade; Harmandeep Singh; Rajender Kumar; Ajay Duseja; Bhagwant Rai Mittal; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Justicia adhatoda floral ethanolic extract exhibits antioxidant, antimicrobial, and apoptosis-inducing effects in human cervical cancer (HeLa) cells via the intrinsic mitochondrial pathway - Ishita Sharma; Jagdeep Kumar; Jiten Yadav; Nishtha Paul; Ajay Kumar; Lovely; Richa Mittal (Journal of Plant Biochemistry and Biotechnology, 2026)

Advancing global standards: Integrating policies for effective management of contaminated sites in India - Jagannath Biswakarma; Kavitha M. Sambasivam; Ajay Kumar; Vinit Kumar Mittal; Asif Qureshi; Ravi Naidu (Environmental Development, 2026)

Sustainable photocatalytic detoxification of organic azo dyes using nickel manganite spinel nanoparticles - Akshita Mittal; Sameena R. Mulani; Ajay Patil; Santosh Bimli; Ekta Choudhary; Suman Yadav; Aayushi Miglani; Rajendra Bunkar; Yuan-Ron Ma; Rupesh S. Devan (Journal of Water Process Engineering, 2025)

Pillared interlayered clays in adsorption and advanced oxidation processes: A sustainable approach for green chemistry - Baneesh Patial; Navdeep; Nitten Kumar; Ajay Bansal; Renu Gupta; Susheel K. Mittal (Applied Clay Science, 2025)

Incorporation of omega-3 enriched shrimp oil nanoliposomes in threadfin bream surimi gel: Gel properties, oxidative stability, and bioavailability assessed via Caco-2 cells - Soottawat Benjakul; Jirakrit Saetang; Ajay Mittal; Eng Keng Seow; Avtar Singh (Food Bioscience, 2025)

Development of a novel amperometric biosensor utilising Chlorella sp. for determination of organophosphorus pesticides - Baneesh Patial; Manisha Pabbi; Shreya Gupta; Susheel K. Mittal; Ajay Bansal; Renu Gupta (Bioresource Technology Reports, 2025)

Sous vide and chitooligosaccharide-catechin conjugate for inactivation of Vibrio parahaemolyticus and Shewanella algae in refrigerated Asian green mussel - Suriya Palamae; Ajay Mittal; Jirakrit Saetang; Natchaphol Buamard; Lukai Ma; Bin Zhang; Soottawat Benjakul (Food Control, 2025)

HIV associated motor neuron disease (MND): A case series with systematic review of literature - Farsana Mustafa; Sapna Mittal; Divyani Garg; Ayush Agarwal; Ajay Garg; Baidnath Kumar Gupta; Manish Soneja; Achal Kumar Srivastava (Journal of NeuroVirology, 2025)

Chitooligosaccharide-epigallocatechin gallate conjugate ameliorates lipid accumulation and promotes browning of white adipose tissue in high fat diet fed rats - Kanokrada Tonphu; Sirikul Mueangaun; Natcha Lerkdumnernkit; Jirakhamon Sengking; Jiraporn Tocharus; Soottawat Benjakul; Ajay Mittal; Chainarong Tocharus (Chemico-Biological Interactions, 2025)

Chitooligosaccharide-catechin conjugate and high-pressure processing: Microbial control and quality preservation of baby clam during refrigerated storage - Suriya Palamae; Ajay Mittal; Bin Zhang; Soottawat Benjakul (Food Bioscience, 2024)

Pacific white shrimp (Litopenaus vannamei) treated with chitooligosaccharide-catechin conjugate with the aid of prior pulse electric field and vacuum impregnation: Quality and microbial diversity during refrigerated storage - Ajay Mittal; Suriya Palamae; Avtar Singh; Bin Zhang; Soottawat Benjakul (Food Bioscience, 2024)

Assessment of triclosan induced histopathological and biochemical alterations, and molecular docking simulation analysis of acetylcholinesterase enzyme in the gills of fish, Cyprinus carpio - Anchal Tripathi; Tuhina Gayen; Priyasha Maitra; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Environmental Science and Pollution Research, 2024)

Biochar supported Ag/Cu-ZrO2 nano-hetero assembly for enhanced adsorption of heavy metal ions and biomedical applications - Deepak Pathania; Ajay Kumar; Adesh K. Saini; Reena Saini; Divya Mittal; Arush Sharma (Nanotechnology for Environmental Engineering, 2024)

Alterations in certain immunological parameters in the skin mucus of the carp, Cirrhinus mrigala, infected with the bacteria, Edwardsiella tarda - Jyoti Singh; Ayan Srivastava; Ashwini Kumar Nigam; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Fish Physiology and Biochemistry, 2023)

Hydrothermal synthesis of (m-t)BiVO4/g-C3N4 heterojunction for enhancement in photocatalytic degradation of imidacloprid - Baneesh Patial; Ajay Bansal; Renu Gupta; Susheel K. Mittal (Journal of Environmental Chemical Engineering, 2023)

Chitooligosaccharide-catechin conjugate: Antimicrobial mechanisms toward Vibrio parahaemolyticus and its use in shucked Asian green mussel - Suriya Palamae; Ajay Mittal; Jirayu Buatong; Bin Zhang; Hui Hong; Soottawat Benjakul (Food Control, 2023)

Ecotoxicological impacts of environmentally relevant concentrations of aspirin in the liver of Labeo rohita: Biochemical and histopathological investigation - Tuhina Gayen; Anchal Tripathi; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Chemosphere, 2023)

α-amylase inhibitory activity of chitooligosaccharide from shrimp shell chitosan and its epigallocatechin gallate conjugate: kinetics, fluorescence quenching and structure–activity relationship - Ajay Mittal; Avtar Singh; Soottawat Benjakul (Food Chemistry, 2023)

Immunoprotective role of aloin and disease resistance in Labeo rohita, infected with bacterial fish pathogen, Aeromonas hydrophila - Ayan Srivastava; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Environmental Science and Pollution Research, 2022)

Numerical simulation of pedestrian level wind conditions: effect of building shape and orientation - Hemant Mittal; Ashutosh Sharma; Ajay Gairola (Environmental Fluid Mechanics, 2020)

Alterations in the epidermis of the carp, Labeo rohita (Cyprinidae: Cypriniformes), infected by the bacteria, Aeromonas hydrophila : A scanning electron microscopic, histopathological and immunohistochemical investigation - Ayan Srivastava; Arup Mistri; Swati Mittal; Ajay Kumar Mittal (Journal of Fish Diseases, 2020)
This study was carried out to comprehend the pathogenicity of the bacteria in the epidermis of Labeo rohita inoculated with Aeromonas hydrophila . Alterations in the histopathology of the epidermis were examined using scanning electron microscopy, light microscopy and the localization of iNOS and caspase 3 + ve cells by means of immunohistochemical methods. Skin samples obtained from infected fish at different intervals 2, 4, 6, 8 and 10 days showed significant changes in the cellular components of the epidermis. Epithelial cells often appeared hypertrophied with fragmented and loosely arranged microridges, and in the process of exfoliation. Mucous goblet cells increased significantly in density. Club cells showed degenerative changes, often with simultaneous confluence of adjacent cells and release of their contents. Increase in density of iNOS and caspase 3 + ve cells indicates inflammatory response and apoptosis. This study could provide valuable information on the pathogenesis of the disease, and disease outbreaks in farmed fish. Further, it could provide useful guidelines for fish farmers to take preventive measures for the control of the disease.

Development of earthquake early warning system for Kachchh, Gujarat, in India using τc and Pd - Santosh Kumar; Himanshu Mittal; Ketan Singha Roy; Yih-Min Wu; Richa Chaubey; Ajay Pratap Singh (Arabian Journal of Geosciences, 2020)

Wind-induced forces and flow field of aerodynamically modified buildings - Ashutosh Sharma; Hemant Mittal; Ajay Gairola (Environmental Fluid Mechanics, 2019)

Characterisation of cholinesterases in mucous secretions and their localisation in epidermis of Labeo rohita and Cirrhinus mrigala - Ashwini Kumar Nigam; Neeraj Verma; Ayan Srivastava; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Fish Physiology and Biochemistry, 2019)

Alterations in the activity of certain enzymes in the gills of a carp Labeo rohita exposed to an azo dye, Eriochrome black T: a biochemical investigation - Ayan Srivastava; Usha Kumari; Ashwini Kumar Nigam; Swati Mittal; Ajay Kumar Mittal (Fish Physiology and Biochemistry, 2018)

Alterations in the skin of Labeo rohita exposed to an azo dye, Eriochrome black T: a histopathological and enzyme biochemical investigation - Ayan Srivastava; Neeraj Verma; Arup Mistri; Brijesh Ranjan; Ashwini Kumar Nigam; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Environmental Science and Pollution Research, 2017)

Role of cardiac TBX20 in dilated cardiomyopathy - Anupam Mittal; Rajni Sharma; Rishikesh Prasad; Ajay Bahl; Madhu Khullar (Molecular and Cellular Biochemistry, 2016)

Integrated Assessment of no-Regret Climate Change Adaptation Options for Reservoir Catchment and Command Areas - Ajay Gajanan Bhave; Neha Mittal; Ashok Mishra; Narendra Singh Raghuwanshi (Water Resources Management, 2016)

Impact of Human Intervention and Climate Change on Natural Flow Regime - Neha Mittal; Ajay Gajanan Bhave; Ashok Mishra; Rajendra Singh (Water Resources Management, 2016)

Characterization of carboxylesterase in skin mucus of Cirrhinus mrigala and its assessment as biomarker of organophosphate exposure - Ashwini Kumar Nigam; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Fish Physiology and Biochemistry, 2014)

Comparative analysis of innate immune parameters of the skin mucous secretions from certain freshwater teleosts, inhabiting different ecological niches - Ashwini Kumar Nigam; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (Fish Physiology and Biochemistry, 2012)

Internet resources and biochemistry - H. K. Bid; Ajay Kumar; R. D. Mittal (Indian Journal of Clinical Biochemistry, 2006)